Implementing Trauma-Informed Strategies for Mothers of Infants with Neonatal Abstinence Syndrome. Issue 4 (July 2021) - Linn, Natalie; Stephens, Kimberly; Swanson-Biearman, Brenda; Lewis, Deborah; Whiteman, Kimberly
Abstract: Purpose: To improve outcomes of infants with neonatal abstinence syndrome (NAS) by implementing an evidence-based approach to care. Methods: An interdisciplinary team developed and implemented an educational module about the elements and principles of trauma-informed care (TIC) and standardized education on NAS for mothers with substance use disorder (SUD). The team collaborated with community behavioral health professionals to secure the services of a certified recovery specialist. Primary outcome measures of average length of stay (LOS) and admissions to special care nursery (SCN) for NAS infants were analyzed. Results: Following health care team education on TIC and implementation of the standardized NAS brochure, average LOS decreased significantly from 6.5 to 5.1 days from baseline period (January–December 2019) to the implementation period (February–June 2020; p = 0.03). There was no difference in SCN admission from the baseline period (February–June 2019) to the implementation period (February–June 2020). Referrals to certified recovery specialists did not change. Clinical Implications: Education on the impact of trauma on new mothers with SUD can promote collaboration between them and the neonatal team. Standardizing education for new mothers of infants with NAS can help to engage families of infants with NAS and improve clinical outcomes. Abstract : Trauma-informed care was the basis for this quality improvement project to help neonatal nurses and physicians learn about how to best provide care for women with substance use disorders and their infants with neonatal abstinence syndrome. Details of the program are offered with suggestions for implementation.